ANALYSIS OF THE EFFECT OF THE IMPLEMENTATION OF TQM ON QUALITY COSTS - WICAKSONO, BUDIAWAN AJI; SUNARKO, BAMBANG (INDONESIAN RESEARCH SOCIETY, 2019)
The research objective is to analyse the influence of focus on customers, obsession withquality, education and training, benchmarking, teamwork and continuous improvement inquality costs. The hypothesis proposed is Customer Focus, obsession with Quality,Education and Training, Benchmarking, Teamwork and Continuous Improvement affectquality costs. The number of respondents taken in this study was 80 respondents. Theanalytical tool used is using the SPSS application program with techniques. Multipleregression analysis and hypothesis testing using f and t-test.